Sistem Proteksi Arus Lebih dengan Menggunakan SEPAM 1000+ T40 pada Transformator di Unit WHRPG PT. Semen Padang : Overcurrent Protection System Using SEPAM 1000+ T40 in the Transformer In The WHRPG Unit PT. Semen Padang - Alfian, Defri (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2024)
The transformer is an important piece of equipment in the WHRPG generator system which functions to change the electric voltage from high to low or vice versa. In the transformer interference can occur which can damage the transformer. Therefore, it is necessary to have proper transformer protection to ensure safe operation and avoid damage that can disrupt the distribution of electric power. So that the related objective of this existing problem is protection is carried out to overcome disturbances that occur in transformers with equipment in the form of SEPAM 1000+ type T40. The method used is by collecting data on power transformer specifications, SEPAM 1000+ specifications and overcurrent relay settings for later analysis and calculations related to the magnitude of the fault current and the magnitude of the relay current setting. Based on the specifications of the transformer and the existing disturbances, the results show that the SEPAM 1000+ T40 in the WHRPG functions to protect the transformer from overcurrent disturbances, ground faults and overload disturbances, for the maximum current value on the transformer is 146.63 A, while the maximum overcurrent disturbance that can occur is 2,443.8 A, so that from the value of the disturbance, an overcurrent elay setting value of 175.95 A is obtained with a relay working time of 0.25 s. Then input the results of the settings earlier into SEPAM 1000+.